Biosensors Current and Novel Strategies for Biosensing - Jesús Villarreal-Gómez, Luis; Leticia Iglesias, Ana (Biomedical Engineering, 2021)
This book covers novel and current strategies for biosensing, from the use of nanomaterials and biological functionalized surfaces to the mathematical assessment of novel biosensors and their potential use as wearable devices for continuous monitoring. Biosensing technologies can be used in the medical field for the early detection of disease, monitoring effectiveness of treatments, detecting nervous system signals for controlling robotic prosthesis, and much more. This book includes eleven chapters that examine and discuss several strategies of biosensing, proposing mathematical designs that address the latest reported technologies.